2020
DOI: 10.3389/fonc.2020.01426
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Tolerant Idling Melanoma Cells Exhibit Theory-Predicted Metabolic Low-Low Phenotype

Abstract: Cancer cells adjust their metabolic profiles to evade treatment. Metabolic adaptation is complex and hence better understood by an integrated theoretical-experimental approach. Using a minimal kinetic model, we predicted a previously undescribed Low/Low (L/L) phenotype, characterized by low oxidative phosphorylation (OXPHOS) and low glycolysis. Here, we report that L/L metabolism is observed in BRAF-mutated melanoma cells that enter a drug-tolerant "idling state" upon long-term MAPK inhibition (MAPKi). Consist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…Two regulatory networks corresponding to proliferative and invasive phenotypes have been identified, with SOX10 and MITF acting as key regulators of the proliferative network and TEAD and AP-1 as regulators of the invasive one. How epigenetic silencing enables reversible or irreversible transitions ( Jia et al., 2019 ) in melanoma, remains to be yet investigated. Besides diverse epigenetic signatures, the proliferative and invasive phenotypes have been characterized to have distinct metabolic profiles too.…”
Section: Discussionmentioning
confidence: 99%
“…Two regulatory networks corresponding to proliferative and invasive phenotypes have been identified, with SOX10 and MITF acting as key regulators of the proliferative network and TEAD and AP-1 as regulators of the invasive one. How epigenetic silencing enables reversible or irreversible transitions ( Jia et al., 2019 ) in melanoma, remains to be yet investigated. Besides diverse epigenetic signatures, the proliferative and invasive phenotypes have been characterized to have distinct metabolic profiles too.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the gene expression profiles of the SKMEL5 subclones (reported by Jia et al . [42]) and observed that the expression of PC is upregulated in the SC10 subclone upon PLX4720 treatment (Fig. 6 B).…”
Section: Resultsmentioning
confidence: 93%
“…2 D in Jia et al . [42]). We further analyzed the gene expression profiles of melanoma tissue samples obtained from patients before and after treatment with a BRAF signaling inhibitor [43] (Gene Expression Omnibus [46] accession GSE75299).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 summarizes the known CSCs' metabolic phenotypes and how these phenotypes switch with metabolic stressors like nutrient deprivation and hypoxia. However, melanoma cells attain a drug-tolerant "idling state" after enduring MAPK inhibition (MAPKi) and this state has a metabolically Low/ Low (L/L) phenotype, where both AMPK/HIF-1 activity and OXPHOS/glycolysis are minimal (189). L/L phenotype does not favor tumorigenicity but supports cell division.…”
Section: Future Challengesmentioning
confidence: 99%